The Escalation of Interethnic Relations in the South-Eastern Province of Poland in the Autumn of 1939 as an Element of the Information-Psychological War of the Stalinist Totalitarian Regime in Modern Ukrainian Discourse - Gulay, Vasyl; Dmytryshyn, Nathalia (Historia i Polityka, 2020)
The purpose of this article is to analyze the causes, nature and consequences of the Ukrainian-Polish-Jewish conflict-confrontational interaction in the Lviv, Stanislav and Ternopil Voivodeships in the autumn of 1939 under the conditions of planting the Stalinist totalitarian regime. It also characterizes the degree and nature of mutual aggressiveness among the part of the active national-political and socially oriented Ukrainian and Polish population of Western Ukraine in the context of the expansion of German aggression against the Second Polish-Lithuanian Commonwealth. It indicates the ideological and propaganda principles for the preparation of the Red Army’s entry into Lviv, Stanislav and Ternopil Voivodeships of Poland on September 17, 1939. The main models of the attitude to the Soviet authorities of the various national communities of Eastern Galicia in the autumn of 1939 are described. Furthermore, the size of the armed struggle between Ukrainians and Poles in the conditions of the collapse of the Polish state and the preparation of the Red Army’s entry into Western Ukraine are shown, as well as the specific propaganda-manipulative instruments of the influence of Stalin’s totalitarian regime on the population of the Western Ukrainian region in the process of its inclusion in the USSR. The paper also indicates the consequences of destructive information-psychological diktat on the public consciousness and historical memory of the Ukrainian, Polish and Jewish population of the former Lviv, Stanislav and Ternopil Voivodeships of pre-war Poland.